A Case Series of Pediatric Intestinal Ganglioneuromatosis With Novel Phenotypic and Genotypic Profile - Yuan Fang; Ye Zhang; Rui Dong; Yi-zhen Wang; Lian Chen; Gong Chen (Frontiers in Medicine, 2022)
IntroductionIntestinal ganglioneuromatosis (IGN) is a rare condition with enteric involvement. Herein, we report a case series of pediatric IGN with a novel phenotypic and genotypic profile.MethodsThe clinical presentation, histopathology, immunochemistry, molecular features, treatment, and prognosis of 3 cases of IGN were assessed.ResultsThe cases involved 3 boys with an age range of 1 year and 4 months to 8 years, mimicking juvenile polyps or pseudomembranous enteritis. One patient carried a novel germline mutation in RTEL1 (c.296C > T/p.Pro99Leu) along with variants in F11 (c.1489C > T/p.Arg497Xaa), NBAS (c.1514delC/p.Pro505Hisfs*15), and FECH (c.315-48T > C/splicing), who died due to intractable inflammation. The other two patients underwent recurrence without significant signs of systemic syndrome or malignant progression.ConclusionThis case series added to the phenotypic and genotypic spectrum of pediatric IGN, which requires the accumulation of more cases and research for in-depth understanding.